Response rate of commonly practiced anti H. pylori therapy among people suffering from H. pylori associated peptic ulcer disease in Bangladesh (BIRDEM Medical Journal, 2025)
Background: H. pylori, a microaerophilic, Gram-negative bacterium in the alimentary canal, causes chronic gastritis and gastric ulcers and is the most important cause of duodenal ulcers and stomach cancer. Infection by H. pylori carries a 10-20% risk of peptic ulcers and 1-2% risk of stomach cancer over lifetime. Prevalence of H. pylori infection varies from country to country depending on food hygiene, sanitation status and living condition. One study showed 92% of populations are seropositive of H. pylori infection in Bangladesh. Eradication of the infection by using antimicrobial has been reported to lower complications. Recently variable resistance to many antimicrobial have raised the question of selecting appropriate combinations to improve the outcome. The objective of the study was to find out the response rate of anti-H. pylori therapies among H. pylori associated peptic ulcer disease in Bangladesh. Methods: This was a prospective comparative study was done in BIRDEM General Hospital between April 2023 to March 2024. Patients who attended at OPD and indoor of Department of GHPD with symptoms of dyspepsia investigated with endoscopy. Dyspeptic patients, on endoscopy showing features of peptic ulcer disease or erosive gastritis, positive Rapid Urease Test (RUT) test on biopsy and positive H. pylori antigen (Ag) test in stool were included in the study. Their demographic parameters were recorded. Then the study populations were randomly distributed into three groups, each group received different anti-H. pylori therapies namely amoxicillin, clarithromycin and proton pump inhibitor (PPI) combinations (Group A), amoxicillin, levofloxacin and PPI combinations (Group B) and amoxicillin, metronidazole and PPI combinations (Group C) for two weeks followed by PPI for another 6 weeks. Two weeks after treatment cessation, stool samples were collected and evaluated to assess H. pylori eradication rate among different groups. Results: Total 114 patients were enrolled for the study, among them 90 were attended for follow up. These 90 subjects were divided into 3 groups. 33 individuals received Amoxicillin and Clarithromycin, they were termed as Group A, 30 individuals Amoxicillin and Levofloxacin termed as Group B and 27 individuals received Amoxicillin & Metronidazole combination termed as Group C. We found response rate of Group A, Group B and Group C were 66.67%, 63.33% and 55.56% respectively. Conclusions: The study demonstrates varying response rates among commonly prescribed Anti H. Pylori therapies with Amoxicillin, Clarithromycin & PPI combinations had highest response rate than other therapies we used & none could achieve optimum response (>80%) indicates a high rate of failure of commonly prescribed Anti H. Pylori therapies.BIRDEM Med J 2025; 15(2): 69-72